Cardiorespiratory interactions previously identified as mammalian are present in the primitive lungfish - Monteiro, Diana A.; Taylor, Edwin W.; Sartori, Marina R. [UNESP]; Cruz, André L.; Rantin, Francisco T.; Leite, Cleo A. C. (American Association for the Advancement of Science (AAAS), 2018)
The present study has revealed that the lungfish has both structural and functional features of its system for physiological control of heart rate, previously considered solely mammalian, that together generate variability (HRV). Ultrastructural and electrophysiological investigation revealed that the nerves connecting the brain to the heart are myelinated, conferring rapid conduction velocities, comparable to mammalian fibers that generate instantaneous changes in heart rate at the onset of each air breath. These respiration-related changes in beat-to-beat cardiac intervals were detected by complex analysis of HRV and shown to maximize oxygen uptake per breath, a causal relationship never conclusively demonstrated in mammals. Cardiac vagal preganglionic neurons, responsible for controlling heart rate via the parasympathetic vagus nerve, were shown to have multiple locations, chiefly within the dorsal vagalmotor nucleus thatmay enable interactive control of the circulatory and respiratory systems, similar to that described for tetrapods. The present illustration of an apparently highly evolved control systemfor HRV in a fish with a proven ancient lineage, based on paleontological, morphological, and recent genetic evidence, questions much of the anthropocentric thinking implied by some mammalian physiologists and encouraged by many psychobiologists. It is possible that some characteristics of mammalian respiratory sinus arrhythmia, for which functional roles have been sought, are evolutionary relics that had their physiological role defined in ancient representatives of the vertebrates with undivided circulatory systems.